Pendidikan Agama Kristen Melalui Musik Kas Teh di Tobelo Halmahera Utara - Angelbest Samalagi; Ellen Kambey; Deflita R.N. Lumi (Peneliti.net, 2022)
The purpose of this study is to examine and decrypt how Christian religious education through music Kas Teh in Tobelo. In terms of Christian education, this music is very good to be preserved and developed in the community and church because the educational value contained in it is very high. This research is qualitative research conducted in Tobelo North Halmahera. The lack of awareness of the community and church in Tobelo towards the Christian values contained in this music is one of the reasons researchers raised the title